In vivo chronic nicotine exposure differentially and reversibly affects upregulation and stoichiometry of α4β2 nicotinic receptors in cortex and thalamus. (September 2016) - Fasoli, F.; Moretti, M.; Zoli, M.; Pistillo, F.; Crespi, A.; Clementi, F.; Mc Clure-Begley, T.; Marks, M.J.; Gotti, C.
Abstract: Studies with heterologous expression systems have shown that the α4β2 nicotinic acetylcholine receptor (nAChR) subtype can exist in two stoichiometries (with two [(α4)2 (β2)3 ] or three [(α4)3 (β2)2 ] copies of the α subunit in the receptor pentamer) which have different pharmacological and functional properties and are differently regulated by chronic nicotine treatment. However, the effects of nicotine treatment in vivo on native α4β2 nAChR stoichiometry are not well known. We investigated in C57BL/6 mice the in vivo effect of 14-day chronic nicotine treatment and subsequent withdrawal, on the subunit expression and β2/α4 subunit ratio of 3 H–epibatidine labeled α4β2*-nAChR in total homogenates of cortex and thalamus. We found that in basal conditions the ratio of the β2/α4 subunit in the cortex and thalamus is different indicating a higher proportion in receptors with (α4)2 (β2)3 subunit stoichiometry in the thalamus. For cortex exposure to chronic nicotine elicited an increase in receptor density measured by 3 H–epibatidine binding, an increase in the α4 and β2 protein levels, and an increase in β2/α4 subunit ratio, that indicates an increased proportion of receptors with the (α4)2 (β2)3 stoichiometry. For thalamus we did not find a significant increase in receptor density, α4 and β2 protein levels, or changes in β2/α4 subunit ratio. All the changes elicited by chronic nicotine in cortex were transient and returned to basal levels with an average half-life of 2.8 days following nicotine withdrawal. These data suggest that chronic nicotine exposure in vivo favors increased assembly of α4β2 nAChR containing three β2 subunits. A greater change in stoichiometry was observed for cortex (which has relatively low basal expression of (α4)2 (β2)3 nAChR) than in thalamus (which has a relatively high basal expression of (α4)2 (β2)3 nAChR). Graphical abstract: Highlights: In vivo chronic nicotine exposure up-regulates α4β2 nAChRs more markedly in the cortex than in the thalamus. Chronic nicotine treatment increases the proportion of the (α4)2 (β2)3 stoichiometry in the cortex but not in the thalamus. α4β2 nAChR upregulation and changes in its stoichiometry are transient with an average half-time of 2.7 days.